Cubical accessibility and bounds on curves on surfaces. Issue 4 (6th November 2017) - Beeker, Benjamin; Lazarovich, Nir
Abstract: We bound the size of d ‐dimensional cubulations of finitely presented groups. We apply this bound to obtain acylindrical accessibility for actions on CAT(0) cube complexes and bounds on curves on surfaces.